2022
DOI: 10.3389/fenvs.2022.944383
|View full text |Cite
|
Sign up to set email alerts
|

Would the Urban Environmental Legislation Realize the Porter Hypothesis? Empirical Evidence Based on Panel Data of Chinese Prefecture Cities

Abstract: The Porter hypothesis suggests that well-designed environmental regulation can trigger regional technological innovation that helps gain competitiveness. Little attention has been paid to whether China’s urban environmental legislation supports Porter hypothesis (PH). An empirical test was conducted based on panel data of 218 prefecture-level cities during 2003–2017 to examine the effects of urban environmental legislation on innovation and green total factor productivity (green TFP). The findings reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…However, with improvements in technological innovation, its innovation effect will gradually emerge. The impact of environmental regulation on the upgrading of industrial structure is in a "U"-shaped relationship in the central and western regions, which is inconsistent with Zhang and Lin (2022). This shows that with the improvement of environmental regulation intensity, pollution-intensive industries face higher compliance and cost and have stronger internal motivation to carry out technological innovation and optimize the structure, which is conducive to promoting the advanced industrial structure.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, with improvements in technological innovation, its innovation effect will gradually emerge. The impact of environmental regulation on the upgrading of industrial structure is in a "U"-shaped relationship in the central and western regions, which is inconsistent with Zhang and Lin (2022). This shows that with the improvement of environmental regulation intensity, pollution-intensive industries face higher compliance and cost and have stronger internal motivation to carry out technological innovation and optimize the structure, which is conducive to promoting the advanced industrial structure.…”
Section: Discussionmentioning
confidence: 94%
“…Wang et al (2022) found that the interaction between ER and technological innovation strengthens the role of technological innovation and environmental regulation in the upgrading and rationalization of industrial structures. Zhang and Lin (2022) found that formal environmental regulations weaken the industrial structure adjustment effect of technological innovation. He and Zheng (2023) found that technological innovation is an important means for environmental regulation to promote industrial advancement.…”
Section: Literature Reviewmentioning
confidence: 99%